New Insights into The Pathogenesis of Intrabile Duct Ectopic Hepatocellular Carcinoma: A Case Report and Review of the Literature - Nakamura, Kosuke; Nishi, Takeshi; Hayashi, Hikota; Kawabata, Yasunari; Araki, Asuka; Tajima, Yoshitsugu (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Intrabile duct ectopic hepatocellular carcinoma is an extremely rare clinical entity and its pathogenesis, as well as clinical features, are unclear. Case Presentation: An 83-year-old man was identified with a tumor within the left hepatic duct upon abdominal computed tomography (CT) examination. The tumor, 40×20 mm, showed early enhancement in the arterial- and delayed-phase washout upon contrast-enhanced CT scaning. No tumor lesions were detected in the liver. Endoscopic retrograde cholangiography (ERC) demonstrated a round defect in the left hepatic duct, and biopsy results indicated adenocarcinoma. With a diagnosis of malignant intraductal papillary neoplasm of the bile duct, a left hepatic lobectomy was performed. The surgical specimen revealed an intraductal tumor protruding from the mucosal layer of the left hepatic duct. Histologically, the tumor showed features of poorly differentiated hepatocellular carcinoma without any invasion of the bile duct wall. The tumor was composed of cancer cells with no residual normal liver tissue around the tumor. The liver showed no findings of chronic liver disease or neoplastic lesions. The tumor was finally diagnosed as intrabile duct ectopic hepatocellular carcinoma. The proliferation of the peribiliary glands was evident in the left hepatic duct near the tumor, and the glandular epithelial cells were positive for CD56/NCAM, CD133, and SOX17 upon immunohistochemistry analysis, which is a marker for stem/precursor cells and transcription factors. Conclusions: These findings provide new insights into the pathogenesis of intrabile duct ectopic hepatocellular carcinoma through biliary tree stem/precursor cells in the peribiliary glands.